The rise of elite short-course triathlon re-emphasises the necessity to transition efficiently from cycling to running - Walsh, J. A. (Sports, 2019)
Transitioning efficiently between cycling and running is considered an indication of overall performance, and as a result the cycle-run (C-R) transition is one of the most researched areas of triathlon. Previous studies have thoroughly investigated the impact of prior cycling on running performance. However, with the increasing number of short-course events and the inclusion of the mixed relay at the 2020 Tokyo Olympics, efficiently transitioning from cycle-run has been re-emphasised and with it, any potential limitations to running performance among elite triathletes. This short communication provides coaches and sports scientists a review of the literature detailing the negative effects of prior variable-cycling on running performance experienced among elite, short-course and Olympic distance triathletes; as well as discussing practical methods to minimise any negative impact of cycling on running performance. The current literature suggests that variable-cycling negatively effects running ability in at least some elite triathletes and that improving swimming performance, drafting during cycling and C-R training at race intensity could improve an athlete`s triathlon running performance. It is recommended that future research clearly define the performance level, competitive format of the experimental population and use protocols that are specific to the experimental population in order to improve the training and practical application of the research findings. View Full-Text Keywords: cycle-run; transition; triathlon; performance; elite; training